ENHANCING OCCUPATIONAL SAFETY IN HYDROJET WATER-POLYMER PERFORATION OF WELLS - Pashchenko, A. V.; Perkun, I. V.; Pogrebnyak, V. G. (Systems and Technologies, 2025)
The article focuses on the relevance of ensuring safe working conditions during hydrojet water-polymer perforation of wells – a modern innovative non-explosive technology that is actively implemented in oil and gas extraction and production intensification processes. This approach significantly reduces the risks associated with the use of traditional explosive methods; however, it introduces new safety requirements, particularly due to the application of high pressures. The analysis identifies the main sources of danger associated with this technology: exceeding the permissible pressure level, the likelihood of hydraulic shock, and operator errors that may lead to emergency situations. To reduce the impact of the human factor and minimize risks, the introduction of automated control systems for the technological process is proposed, through the creation of intelligent sensor systems for high-pressure monitoring. For this purpose, a magnetic La0.6Sr0.3Mn1.1O3 (LSMO) nanopowder has been synthesized by atomization hydrolysis and compacted under different pressures up to 1600 MPa. Their phase composition, crystal structure, morphology, magnetic, magneto-resonance, transport, magnetoresistance, and baroresistance properties have been comprehensively studied. As the pressure increases to 1600 MPa, the filling factor in the compacts increases, decreasing the average distance between particles. In the room temperature range, the LSMO nanopowder is in a ferromagnetic state with a Curie temperature 367 oK and does not depend on the compacting pressure. With increasing pressures, a monotonic decrease in resistivity is due to reducing the distance between particles. Giant baroresistance effect with the establishment of the following important applied properties has been found: baroresistance effect is not limited by the Curie temperature and is observed both in the ferromagnetic and paramagnetic states; the baroresistance effect under constant pressure slightly depends on the temperature in a wide range from – 193 to + 127 ℃; in the pressure range from 0 to 400 MPa, the baroresistance effect has the highest sensitivity, which is 0.1%/MPa. The conclusion is made regarding the feasibility of implementing LSMO in safe control systems for hydrojet water-polymer perforation of oil and gas wells.